2021
DOI: 10.3390/s21227452
|View full text |Cite
|
Sign up to set email alerts
|

Mode Sensitivity Exploration of Silica–Titania Waveguide for Refractive Index Sensing Applications

Abstract: In this paper, a novel and cost-effective photonic platform based on silica–titania material is discussed. The silica–titania thin films were grown utilizing the sol–gel dip-coating method and characterized with the help of the prism-insertion technique. Afterwards, the mode sensitivity analysis of the silica–titania ridge waveguide is investigated via the finite element method. Silica–titania waveguide systems are highly attractive due to their ease of development, low fabrication cost, low propagation losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The research on the silica-titania platform demonstrates extraordinary attributes such as low-cost WG technology development, low transmission loss, and chemical resistance to oxidation [186]. This opens up the doors for this technology to compete with the existing mainstream integrated photonics platforms, especially in low-volume niche applications such as sensing [187]. The silica-titania PIC technology was designed from the start to be a low-cost option for possible application by SMEs or less-developed research organizations.…”
Section: Future Goals and Challengesmentioning
confidence: 99%
“…The research on the silica-titania platform demonstrates extraordinary attributes such as low-cost WG technology development, low transmission loss, and chemical resistance to oxidation [186]. This opens up the doors for this technology to compete with the existing mainstream integrated photonics platforms, especially in low-volume niche applications such as sensing [187]. The silica-titania PIC technology was designed from the start to be a low-cost option for possible application by SMEs or less-developed research organizations.…”
Section: Future Goals and Challengesmentioning
confidence: 99%
“…As part of the HYPHa project, the team is involved in the design and testing of optical elements and systems built on the SiOx: TiOy waveguide layer technology, which includes both passive and active components such as integrated optical filters and optically pumped amplifiers. Based on the technology established in the HYPHa project, the team will also spearhead the effort to build sensory system demonstrations and an integrated optical signal source [7,8].…”
Section: Wroclaw University Of Science and Technology Consortiummentioning
confidence: 99%
“…For improved light coupling, the etch depth and the filling factor should be changed during the optimization process [13]. Consequently, we have numerically demonstrated refractive index sensing devices based on ring resonator [7], subwavelength grating waveguide (SWG) and 1D-Photonic crystal waveguide (PhC) as shown in Fig. 2 (ac).…”
Section: Wroclaw University Of Science and Technology Consortiummentioning
confidence: 99%
“…Because of this, thickness control is important for all thin-film development methods, including sol-gel. It has been reported that the coating speed, angle of inclination, and sol concentration have a major role in determining the ultimate thickness [33,34,35]. In addition, the ultimate heat-treated thickness can also be influenced by the sol viscosity, density, and liquid-vapor surface tension [36].…”
Section: Dip-coatingmentioning
confidence: 99%